ANUITAS DI PERBANKAN SYARIAH - Wahyuni, Mirasanti (PRESTASI, 2014)
Â Abstract Â This article discusses the differences annuity method and proportional method of financing murabaha Islamic bank by means of a simulation calculation of both methods is then analyzed. From the simulation results obtained calculation that the amount of the installment to be paid customers is the same each period. There are differences in the amount of the principal and installments margin. When using the proportional method, the amount of the principal and installments margin of each period would be as great. If using the annuity method, the amount of principal will be greater the longer the installment margin but the longer it will be smaller. The amount payable is the same kind of customers using the annuity method or the proportional method, the principal installments and installment loan margins. Â Keyword : the annuity method, the proportional method, financing murabahah